Nutrition Facts use in relation to eating behaviors and healthy and unhealthy weight control behaviors: Original Research Article - Christoph, Mary J (J Nutr Educ Behav, 2017)
OBJECTIVE: Investigate the relationship between use of Nutrition Facts labels on packaged foods and weight-related behaviors. DESIGN: Cross-sectional survey in 2015–2016. PARTICIPANTS: Young adult (N = 1,817, 57% women, average age 31.0 ± 1.6) respondents to the Project EAT (Eating and Activity in Teens and Young Adults)-IV survey, the fourth wave of a longitudinal cohort study. VARIABLES MEASURED: Use of Nutrition Facts labels on packaged foods; healthy, unhealthy, and extreme weight-control behaviors; intuitive eating; binge eating. ANALYSIS: Linear and logistic regression models were adjusted for age, ethnicity/race, education, income, and weight status. RESULTS: In women, greater Nutrition Facts use was associated with a 23% and 10% greater likelihood of engaging in healthy and unhealthy weight control behaviors, respectively, and a 17% greater chance of engaging in binge eating. In men, greater label use was associated with a 27% and 17% greater likelihood of engaging in healthy and unhealthy weight control behaviors, respectively, and a lower level of intuitive eating. CONCLUSIONS AND IMPLICATIONS: Messaging concerning healthy use of Nutrition Facts may be needed; health professionals may consider asking clients at risk for disordered eating behaviors about how they may use labels.